Making friends: amity in American foreign policy - Thompson, M (2015)
This thesis examines an important but understudied phenomenon in international politics: the role of amity in foreign policy. The core research question is "how have American friendships for specified others been made possible?" Drawing on the logic of securitization, this thesis employs Aristotle's notion of character friends as Other Selves and Judith Butler's concept of performativity to elaborate an international process of friendship or amitization. In doing so, the thesis employs critical discourse analysis of presidential rhetoric and popular culture to elucidate the process through which discourses of similarity become naturalized frames of reference within the conduct of foreign policy. It argues that friendship emerges when a state comes to see itself in an other and that this similarity (re)produces a certain form of state identity that enables and forecloses certain policy options vis-à-vis friends. Friendship manifests in a habitual, or naturalized, disposition to treat friends better than others. As such, it can account for how certain policies and postures, such as uncritical and often unconditional support for subjects positioned as "friends," have come to be pursued as common sense. Amitization is illustrated by assessing three case studies: the Anglo-American "special relationship;" the US-Israel "unbreakable bond;" and America's membership of "the Atlantic Community." Specifically, the thesis similarly demonstrates the ways in which amity accounts for how supererogatory commitments such as vast financial assistance, diplomatic support, information sharing, security guarantees and concern for the welfare of these specified others have come to be seen as unquestionably legitimate policies in the broader trajectory of American foreign policy. Amity matters and the practices of amitization are inseparable from intelligible foreign policy.